The hydroid and medusa of Amphinema rollinsi (Cnidaria: Hydrozoa), a new species of pandeid from the Monterey Bay Submarine Canyon, USA - Widmer, Chad L. (Zootaxa, 2007)
A new species of pandeid hydromedusa is described from the Monterey Bay Submarine Canyon, California. Using a remotely operated vehicle, hydroid colonies were collected from artificial substrates that had been emplaced there at a depth of 1019m for five months. Material was returned alive to the laboratory and placed in culture. Medusae released from the hydroids were raised to maturity. Both hydroids and medusae possessed morphological characters corresponding to the genus Amphinema, but neither stage matched descriptions of those of any known species in the genus. Amphinema rollinsi, sp. n., is described herein based on characters of the field-collected hydroid colonies and their laboratory-raised medusae.